The Quranic Manifesto of Moral Rules in the Formation of Islamic Society: In the Context of Surah Al-Hujurat - Nabeela Shafi (Journal of Religion and Society, 2024)
Surah Al-Hujurat is a part of the Holy Quran, and the Quran itself is Divine revelation. It serves as a means of drawing closer to Allah, a timeless elixir for humanity, and the source of all knowledge. It is a compilation of guidance, a treasury of mercy, and a fountain of blessings. It is a constitution that, if followed, can resolve all matters of life. It is a light that dispels all darkness of misguidance, a path that leads directly to the pleasure of Allah and Paradise. It is a system of moral and spiritual training that purifies human beings, making them exemplary in character. It is a tree under whose shade one finds inner peace. It is a loyal companion that stands by one even in the grave and fulfills its promise on the Day of Resurrection.Human beings, by nature, are social creatures. Every individual requires food, clothing, and shelter to survive, and marriage for the continuation of progeny. To obtain these necessities, if there were no law or regulation, the powerful would seize them from the weak by force. Therefore, to establish justice and fairness, a law is necessary. If this law were created by humans, it would inevitably carry personal biases and interests. Hence, it is essential that this law be divinely ordained, free from partiality or suspicion. Such a law could only be the law of God, knowledge of which comes through His revelation. Allah, for the guidance and well-being of all humanity, has granted this law in the form of the Quran. The Quran is the only book that serves as a source of guidance and enlightenment for the entire human race. In this book of guidance, Allah has explained, in detail, all the issues that a human being may encounter.One of the key themes of this Surah is the establishment of a Muslim society—an ideal Muslim community whose example serves the world. A society whose hearts are pure, thoughts are clean, language is virtuous, and inner character is righteous; a society that observes proper etiquette with Allah, follows the adab of the Prophet Muhammad ﷺ, maintains personal discipline, and upholds courtesy towards others in both conscience and actions. This society has established organized rules for its functioning, a system that safeguards it, and these rules and institutions are rooted in adab, aligned with moral etiquette, and reflect the values upon which the society’s spiritual and material world depends. The consciousness, laws, and regulations of such a society are harmonious, allowing it to progress while maintaining balance within its boundaries, ensuring that both actions and intentions remain moderate and oriented toward Allah. Keyword: Quranic studies, Quranic principles, Surah Al-Hujurat, Reconstruction of society, Contemporary relevance of Quranic teachings, Essays on Surah Al-Hujurat